2014
DOI: 10.1111/vec.12139
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic evaluation of hemostatic function in dogs treated for crotalid snake envenomation

Abstract: A hypocoagulable TEG tracing, particularly a decreased G value and MA, is associated with an increased mortality in crotaline snake envenomation. G and MA also demonstrate a significant increase over treatment time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The current in vitro study could not entirely replicate the interactions in complicated living organisms; thus, hyperfibrinolysis was excluded [38]. In patients with natural snake envenomation as a result of a snake bite, the common coagulopathy reported using TEG was delayed fibrinolysis [39,40], and LY30 provided information on fibrinolysis before the decrease in fibrinogen concentrations [33]. As such, even though this study did not result in any valid conclusions in relation to LY30 as it focused on detecting early VICC, LY30 can provide useful information about hyperfibrinolysis in clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…The current in vitro study could not entirely replicate the interactions in complicated living organisms; thus, hyperfibrinolysis was excluded [38]. In patients with natural snake envenomation as a result of a snake bite, the common coagulopathy reported using TEG was delayed fibrinolysis [39,40], and LY30 provided information on fibrinolysis before the decrease in fibrinogen concentrations [33]. As such, even though this study did not result in any valid conclusions in relation to LY30 as it focused on detecting early VICC, LY30 can provide useful information about hyperfibrinolysis in clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…The mortality rate was lower in dogs with a hypercoagulable profile than in those with a hypocoagulable profile, and G values were significantly higher in survivors than in nonsurvivors. Other studies demonstrated that dogs with a hypocoagulable profile had a higher mortality rate than those with a hypercoagulable profile in DIC, in crotalid snake envenomation, and in immune‐mediated hemolytic anemia . This relationship brings into question the role of coagulation in inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…TEG has been utilized previously to document and monitor coagulation changes in cases of envenomation before and after treatment 4,8,10,11,20–23 . Studies have shown that patients envenomated by pit vipers were most likely to be hypocoagulable on TEG analysis, meaning that they have lower coagulation potential than normal patients, which may or may not relate to in vivo coagulation 4,8,10,11,20–23 .…”
Section: Discussionmentioning
confidence: 99%